Flicker-Defined Forms in the Ternus Display. (March 2015) - Silva, Molly R; Petersik, J Timothy
Odic and Pratt (2008, Perception, 37, 1790–1804) proposed that the type of movement seen in the bistable Ternus display depends on the elements' temporal summation of contrast relative to the background. To test this theory, participants viewed a flicker-defined Ternus display where the elements had no temporal summation of contrast. Participants also viewed a luminance-defined control condition. Five interstimulus intervals (ISIs) (0, 20, 40, 60, and 80 ms) and two stimulus durations (SDs) (200 and 400 ms) were used in each condition. If temporal summation of contrast does not influence perceived group and end-to-end movement in flicker-defined forms, it was expected that the frequency of their reports would be equal to those in the luminance- defined control condition at the same ISIs and SDs. As predicted, the main effect of condition was not significant and participants reported both percepts at expected rates in both conditions, contrary to the predictions of Odic and Pratt (2008).